Treatment Approaches Based on Neuroscientific Data in Patients With Obsessive-Compulsive Disorder - Ansari Asl, Mohammad; Asgari, Parviz; Bakhti, Zahra (International Clinical Neuroscience Journal, 2021)
Background: Obsessive-compulsive disorder (OCD) is a severe psychological disorder that can be very disabling. Recent increasing neuroscientific data about OCD has provided important evidence that has started to change our knowledge about treatment. This paper offers an applied perspective of neuroscience on diagnosis and treatment preparation for people with OCD disease. The main aim is to enhance clinician-researcher communication to promote the conversion of developments in neuroscience research into better treatment for patients with OCD. Methods: A PubMed search was performed using the keywords “obsessive-compulsive disorder”, “neuroimaging methods”, “neuroscience”, and “neurological treatment”. The search provided sufficient articles published in peer-reviewed journals from 1995 to 2021. The data were obtained from these various sources and were included in this review. Results: The advancement of neurotherapeutic techniques targeting the cortico-striatal-thalamo-cortical (CSTC) circuit is the subject of a circuit dysregulation system. Also, according to neuroimaging studies, reductions in D2 receptors (about -18%), GABAA receptors (-15%), and cingulate 5-HT1A receptors (-18%) in patients with OCD were reported compared with healthy controls. Conclusion: The result suggests that DA, 5-HT, and GABA have considerable roles in anxiety- and compulsion-related disorders such as OCD. For patients with OCD, these core neuroscience themes collectively guide formulation and clinical preparation.